A Review of the Effects of Textual Enhancement on Second Language Learning - Guo, Tiantian (International Journal of Linguistics, Literature and Translation, 2023)
Textual enhancement refers to techniques for making target linguistic features in a text more perceptually salient. Textual enhancement has been frequently studied as a promising instructional method for promoting language learning. This paper reviewed studies on the role of textual enhancement in terms of vocabulary and grammar learning, second language speaking, writing, reading, and pragmatic competence. In addition, this paper also pointed out the problems of current research and the direction of future research. To prove the effectiveness of second language learning, researchers should further explore the effects of textual enhancement in various language environments.